Nutrition to support a healthy skeleton - H.V. Beketova; Yu.V. Klymova (Zdorovʹe Rebenka, 2024)
Background. Bone tissue is actively exposed to environmental factors and lifestyle. Since the bone mass accumulated in childhood will determine the state of the skeleton during a person’s subsequent life, it is necessary to promote its maximum increase. Sufficient nutrition is one of the main factors in maintaining bone health. The purpose of our study was to determine the level of daily basic nutrient intake among schoolchildren and to reveal its relationship with clinical disorders of the musculoskeletal system. Materials and methods. Using a computer program, we assessed the actual diet of 65 schoolchildren aged from 8 to 17 years. Results. It was found that 90 % of children were deficient in iodine and calcium, and more than 70 % were deficient in zinc and selenium. The deficiency of potassium, magnesium, iron, copper, fluorine, manganese, and phosphorus was less pronounced. A significant deficiency of vitamin D, β-carotene, vitamin A, biotin, and vitamin E was noted. In almost half of the examined children, the share of saturated fatty acids in the diet exceeds the recommended norm, while the level of polyunsaturated fatty acids is significantly reduced. In 93.8 % of schoolchildren, the nutritional ratio between calcium and phosphorus is disturbed. Conclusions. The obtained results testify to the unbalanced diet of schoolchildren and inconsistency with physiological needs. Deficiency of a number of nutrients can contribute to musculoskeletal pain, convulsive syndrome, fractures, caries and recurrent respiratory disease.